A crosstalk of circadian clock and alternative splicing under abiotic stresses in the plants - Fan, Tao; Aslam, Mehtab Muhammad; Zhou, Jian-Li; Chen, Mo-Xian; Zhang, Jianhua; Du, Shenxiu; Zhang, Kai-Lu; Chen, Yun-Sheng (Frontiers in Plant Science, 2022)
The circadian clock is an internal time-keeping mechanism that synchronizes the physiological adaptation of an organism to its surroundings based on day and night transition in a period of 24 h, suggesting the circadian clock provides fitness by adjusting environmental constrains. The circadian clock is driven by positive and negative elements that regulate transcriptionally and post-transcriptionally. Alternative splicing (AS) is a crucial transcriptional regulator capable of generating large numbers of mRNA transcripts from limited numbers of genes, leading to proteome diversity, which is involved in circadian to deal with abiotic stresses. Over the past decade, AS and circadian control have been suggested to coordinately regulate plant performance under fluctuating environmental conditions. However, only a few reports have reported the regulatory mechanism of this complex crosstalk. Based on the emerging evidence, this review elaborates on the existing links between circadian and AS in response to abiotic stresses, suggesting an uncovered regulatory network among circadian, AS, and abiotic stresses. Therefore, the rhythmically expressed splicing factors and core clock oscillators fill the role of temporal regulators participating in improving plant growth, development, and increasing plant tolerance against abiotic stresses.